2021
DOI: 10.1073/pnas.2022302118
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic and ecological analyses reveal the spatiotemporal evolution of global pines

Abstract: How coniferous forests evolved in the Northern Hemisphere remains largely unknown. Unlike most groups of organisms that generally follow a latitudinal diversity gradient, most conifer species in the Northern Hemisphere are distributed in mountainous areas at middle latitudes. It is of great interest to know whether the midlatitude region has been an evolutionary cradle or museum for conifers and how evolutionary and ecological factors have driven their spatiotemporal evolution. Here, we investigated the macroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
116
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 94 publications
10
116
2
Order By: Relevance
“…We observed that P. koraiensis and P. sibirica maintain relatively close genetic relationship compared with P. pumila . Similar results were reported in previous study of spatiotemporal evolution of global pines ( Jin et al, 2021 ). Furthermore, in subgroup II, P. pumila and P. parviflora were divided into the same group of five-needle pines, which may correspond to the traits of short needles among them.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that P. koraiensis and P. sibirica maintain relatively close genetic relationship compared with P. pumila . Similar results were reported in previous study of spatiotemporal evolution of global pines ( Jin et al, 2021 ). Furthermore, in subgroup II, P. pumila and P. parviflora were divided into the same group of five-needle pines, which may correspond to the traits of short needles among them.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the transcriptome-based phylogeny also shows a very high resolution of interspecific relationships, indicating that phylotranscriptomics is an economical and highly efficient approach for tree of life reconstruction at the species level, even for plant groups with recent evolutionary radiations like Rhododendron or with long generation times and slow molecular evolutionary rates like pines ( Jin et al 2021 ). It is generally recognized that transcriptome sequencing (RNA-seq) needs fresh samples, but actually silica-gel dried plant materials are also suitable for phylotranscriptomic studies according to our experience, because phylotranscriptomics uses OGs generated from RNA-seq and does not compare gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Phenological traits have been linked to seasonal variation within species of North America (Jump and Penuelas 2005), and differences in seasonality requirements for P. pungens and P. rigida likely explain the observed phenological trait differences in seed size, reproductive age, timing of pollen release, and rates of seedling establishment across these two species (Zobel 1969; Della- Bianca 1990; Ledig et al 2015). Using niche and trait data, the phylogenetic inference of Jin et al (2021) identified precipitation seasonality (Bio15) and elevation as drivers of diversification in eastern North American pines. The results of our RDA corroborate these conclusions, as clear separation of species-level genetic differences was explained by Bio15 and elevation along axis 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%